(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Globalization compels changes in the understanding of both affirm andcompetition. People and communication with them becomes the critical component of afirm’s activity. The main marketing problem is to get as much knowledge as possibleabout customers and their behavior in the market. Relationship marketing, also knownas customer-oriented or partnership marketing, was created as the consequence ofchanges in the market in the broader sense of this term. Nowadays the situation in theservice sector undergoes considerable change resulting in important transformationinside an organization and improvement in building relations with customers.